The Influence of Inconsistent Parenting Styles on the Socio-Emotional Development of Early Childhood Children at TKN 1 Bandar Laksamana - Siti isnaini; Emi; Nurhaida Selian (al-Afkar, Journal For Islamic Studies, 2026)
Parenting style is a key factor influencing child development, particularly during early childhood. This study aims to explore the impact of inconsistent parenting on the socio-emotional development of young children at TKN 1 Bandar Laksamana. The findings indicate that inconsistency in the application of discipline and rules at home creates confusion for children, leading to heightened anxiety, difficulties in emotional regulation, and poor social skills. Children raised in inconsistent environments tend to struggle to form healthy relationships with peers and adults, and often exhibit withdrawn or aggressive behaviors. The study also highlights the importance of collaboration between parents and teachers in supporting child development, as well as the need for educational programs to raise parental awareness regarding the importance of consistency in parenting. Ultimately, it is hoped that children can grow up in a stable and supportive environment that enables them to reach their full potential in both social and academic spheres.